Understanding diffusion layer agitation by cavitation in electroplating based on high-speed monitoring - Taisuke Nozawa (Elsevier, 2021)
Ultrasonic electroplating has gained attention owing to various advantages such as the promotion of mass transport to the substrate surface, improvement of the surface properties of the film, and improvement of limiting current density. However, no studies have clarified the mechanism in diffusion layer agitation caused by cavitation during ultrasonic electroplating. Here, we investigate the main factor of agitation by using a high-speed imaging technique to capture the agitation effect of shock waves and microjets generated from laser-induced cavitation on the diffusion layer of electroplating. The physical parameters of the agitation were characterized using image analysis and a micro-pressure gauge. The results revealed that only microjets affected the agitation phenomenon. The flow velocity was 21 m/s, and the water hammer pressure was low, at least below 0.05 MPa. Our results suggest that the flow velocity, and not the water hammer pressure, plays an important role in the agitation phenomenon on the substrate surface by cavitation.